SKIN FRICTION BETWEEN UNDISTURBED OVER CONSOLIDATED SILTY CLAY SOILS AND CONCRETE (Journal of Engineering, 2008)
Up to date, in many foundation design problems (especially for piles foundation), the shear strength (skin friction) between soil and construction materials of the foundation was usually estimated or correlated without any direct methods for measurement.The modern trend is to establish skin friction coefficients through laboratory experiments in which the factors influencing the results may be controlled quantitatively.In this study strain controlled Direct Shear Tests were performed using shear to simulate the shear behavior area between concrete (foundation materials) and undisturbed over consolidated silty clay, to determine the shear strength of soil – foundation interface, considering the following variables : (1) Concrete, smooth surface condition, (2) Undisturbed over consolidated silty clay, (3) Variation of the normal load between the friction surface. The tests conveniently revealed both shear strength parameters as for soil test (cohesion and angle of internal friction), and interface angle of friction was in the range of 14° to 17°, while the adhesion was in the range of 13 to 16 kPa.The ultimate shear strength was mobilized through 4 to 7 mm displacement in the direction of shear slip; this was a great advantage of Direct Shear Test performance.